Electronic and magnetic properties of epitaxial perovskite SrCrO3(0 0 1). (3rd June 2015) - Zhang, K H L; Du, Y; Sushko, P V; Bowden, M E; Shutthanandan, V; Qiao, L; Cao, G X; Gai, Z; Sallis, S; Piper, L F J; Chambers, S A
Abstract: We have investigated the intrinsic properties of SrCrO3 epitaxial thin films synthesized by molecular beam epitaxy. We find compelling evidence that SrCrO3 is a correlated metal. X-ray photoemission valence band and O K-edge x-ray absorption spectra indicate a strongly hybridized Cr3d–O2p state crossing the Fermi level, leading to metallic behavior. Comparison between valence band spectra near the Fermi level and the densities of states calculated using density functional theory (DFT) suggests the presence of coherent and incoherent states and points to strong electron correlation effects. The magnetic susceptibility can be described by Pauli paramagnetism at temperatures above 100 K, but reveals antiferromagnetic behavior at lower temperatures, possibly resulting from orbital ordering.